Interest in Entrepreneurship and Factors That Influence - M. Trihudiyatmanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose - This study aims to see the influence of Self-Confidence, Independence and Family Environment on Entrepreneurial Interest (case study on Students of the Faculty of Economics and Business, Al-Qur'an Science University. Method - The data used in this study was by distributing questionnaires directly to students of the Faculty of Economics and Business. The population was students of the Faculty of Economics and Business, and the sample size was set at 100 respondents, distributed using the Proportional Random Sampling. Data analyzed with using analysis regression linear multiple, then use test statistics descriptive, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, and testing hypothesis covering test coefficient determination and significance test of regression coefficients. Findings - Results study show that variables Believe Self positive influence to interest entrepreneurship student Faculty Economy University of Science Al-Qur'an, Which proven with variables believe self own t count = 5,973 with t table =1.971896 And variable independence has a positive influence on Interest entrepreneurship student Faculty Economy University Science of the Qur'an, Which proven with variables independence own t count = 8.202 with t table = 1.971896, and the family environment has an influence on Interest entrepreneurship student Faculty Economy University Al-Quran Science, which is proven by the family environment variable, has a calculated t = 5.168 with a t table =1.971896 and a significant value of 0.000<0.05.